Pengembangan Media Pembelajaran Fikih berbasis Android untuk Meningkatkan Hasil Belajar Siswa Kelas X MA - Diana, Zuhur; Susilawati, Samsul; Nur, Muhammad Amin (Jurnal Simki Pedagogia, 2026)
Education must adapt to technological developments in order to maximize both the challenges and benefits that arise. The integration of digital technology in classroom learning has become one of the important innovations in contemporary learning. This article describes research and development of Android-based fiqh learning media designed to improve the learning outcomes of 10th grade students in Islamic high schools. This study used an R&D method with the ADDIE model, which consists of five stages from analysis to evaluation. The resulting product is an Android application called Baitullah, which focuses on Hajj and Umrah material. This product was declared highly feasible by three validators, with a percentage of 95% from subject matter experts, 96% from media experts, and 97% from learning practitioners. The responses of 20 students regarding the attractiveness of the product reached a percentage of 87% in the very attractive category. The N-Gain value was recorded at 0.59, indicating sufficient effectiveness. The t-test also yielded a p-value < 0,001, thus rejecting H0 and accepting Ha. It can be concluded from the analysis that there was a significant increase in learning outcomes after using the product, indicating that the Android-based fiqh learning media is effective for learning.